2020
DOI: 10.1002/ddr.21749
|View full text |Cite
|
Sign up to set email alerts
|

Allylphenols as a new class of human 15‐lipoxygenase‐1 inhibitors

Abstract: In this study, a series of mono‐ and diallylphenol derivative were designed, synthesized, and evaluated as potential human 15‐lipoxygenase‐1 (15‐hLOX‐1) inhibitors. Radical scavenging potency of the synthetic allylphenol derivatives was assessed and the results were in accordance with lipoxygenase (LOX) inhibition potency. It was found that the electronic natures of allyl moiety and para substituents play the main role in radical scavenging activity and subsequently LOX inhibition potency of the synthetic inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…found that compounds with a 3–(2-naphthyl)-1-phenyl-1H-pyrazole backbone had good ALOX15 binding potential 19 ; while Alavi et al. in 2021 discovered a series of compounds in Allylphenols were shown to inhibit the binding of ALOX15 and thus further scavenge oxidative radicals 20 . To date, no ALOX15 inhibitors have progressed beyond the preclinical phase and into the realm of therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…found that compounds with a 3–(2-naphthyl)-1-phenyl-1H-pyrazole backbone had good ALOX15 binding potential 19 ; while Alavi et al. in 2021 discovered a series of compounds in Allylphenols were shown to inhibit the binding of ALOX15 and thus further scavenge oxidative radicals 20 . To date, no ALOX15 inhibitors have progressed beyond the preclinical phase and into the realm of therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%